2012
DOI: 10.1159/000343005
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Activity in Patients with Breast Cancer: An Analysis of Plasma, Tumors, and Its Relationship with the Presence of the Estrogen Receptor

Abstract: Background: Breast cancer is an important cause of cancerrelated death in women. In this pathological condition, arginase plays a role by providing ornithine as a substrate for the biosynthesis of polyamines which are important in tumor progression. The aim of this work was to determine the arginase activity in the plasma and tumors of patients with breast cancer; also, we investigated the relationship between this activity and the presence of the estrogen receptor. Patients and Methods: We evaluated the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(80 citation statements)
references
References 22 publications
3
75
0
Order By: Relevance
“…12,13 Clinical studies on breast cancer patients have also demonstrated that serum arginase activity correlates with elevated histological grade. 14,15 Aside from arginase expression in cancer cells themselves, elevated arginase-1 expression in tumor associated macrophages is thought to support an immunosuppressive phenotype that promotes T-cell evasion and tumor growth. 16,17 Thus, there is a strong link between disease progression and arginase expression, and the development of an imaging agent for arginase activity will address an unmet need of significant relevance to biomedical research.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Clinical studies on breast cancer patients have also demonstrated that serum arginase activity correlates with elevated histological grade. 14,15 Aside from arginase expression in cancer cells themselves, elevated arginase-1 expression in tumor associated macrophages is thought to support an immunosuppressive phenotype that promotes T-cell evasion and tumor growth. 16,17 Thus, there is a strong link between disease progression and arginase expression, and the development of an imaging agent for arginase activity will address an unmet need of significant relevance to biomedical research.…”
mentioning
confidence: 99%
“…-arginine in this Article. Following synthesis of this compound, T 1 and T 2 values of the carbon-6 resonance of [6-13 C, 15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To further dissect the mechanism of how infiltrating macrophages can increase the ERa expression in the lung cancer cells, we then examined those reported cytokines that may affect ERa expression (Farmaki et al, 2016;Katz et al, 2013;Kirma et al, 2004;Lazennec and Richmond, 2010;Levano et al, 2011;Ning et al, 2016;Perez et al, 2012;Sakumoto et al, 2017;Sauv e et al, 2009). The results revealed that THP-1 cells might express higher CXCL12 compared with lung cancer A549 and H1299 cells at mRNA levels (Fig.…”
Section: Mechanism Dissection Of How Increasing Infiltrated Macrophagmentioning
confidence: 99%
“…In humans, various leukocyte subpopulations synthesizing arginase may be involved (13). High arginase blood levels have been measured in sera from acute hepatitis B, resulting in T cell function suppression, and in various cancers (14,15,16). High arginase activity has been measured in cutaneous leishmaniasis lesions (17).…”
mentioning
confidence: 99%